TEKNOLOGI BIOFILTER UNTUK PENGOLAHAN LIMBAH AMMONIA - Titiresmi Adyananto (Jurnal Teknologi Lingkungan, 2006)
Ammonia compound is chemical compounds abundance in nature.Ammonia wastes discharge into water body will have a negative impactand cause ecological and healthy problems. High concentration ofammonium will give eutrofication problem in water body therefore dissolveoxygen demand will be decreased as well as self purification of waterecosystem. This negative impact will influenced for aquatic organismwhich died gradually. The efforts decrease of ammonia concentration isby biological waste water treatment utilizing microbes for changingammonia to nitrite and nitrate. One of the technologies could be carriedout is nitrification process technology using biofilter with 80% efficiency.For decreasing ammonia concentration can be used biological treatmentby using microbe which can change it ti nitrite and nitrate